REKAYASA PERANGKAT LUNAK MONITORING HASIL PRODUKSI KEMASAN KAYU BERSTANDAR INTERNATIONAL STANDARD FOR PHYTOSANITARY MEASURE NO.15 (ISPM #15) STUDI KASUS CV.SUMBER REJEKI ID-089 - Sutanto Sutanto; Widyawati Widyawati; Riki Andi Wijaya (Jurnal Ilmiah Sains dan Teknologi, 2019)
Entering the societies of the ASEAN Economy (MEA) that is a realizations of free market in Southeast Asia hopedfully can solve any problems in the economic field between ASEAN countries. As a supporting media for export commodities such as fruits, forest products, industrial products and others, wooden packaging must meet the standard criteria listed in International Standard for Phytosanitary Measure No.15 (ISPM#15), this is because the packaging made of wood is a material containing lignocelluloses that are susceptible to fungi and insects. Considering the risk of severe sanctions imposed by custemers and government through Agricultural Quarantine Agencies, if any discrepancies arise regarding the use of such wooden packaging, the company producing and certifying the wooden packaging will be subjected to sanctions in the form of fines, temporary suspend so that the company is not allowed to operate, or even get the revocation permit No.ID (No. Registration), where this means the company can not operate more to do certify wood packaging or even produce it appropriate with international standard for Phytosanitary Measure No.15 (ISPM#15). So, a hard control and supervising are required in order to identify problem regarding the usage of wood packaging fastly so that they can do any prevention and minimize the findings of nonconformity in the destination country which deals with the prevention of pests on wood material as a packaging media for export commodities in order not to be carried out and grew up in the destination country.